(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation: This article explores the advantages of content-based learning, a pedagogical approach that integrates subject matter content with language learning objectives. It emphasizes the benefits for students, educators, and educational systems alike. The article highlights how content-based learning enhances engagement and motivation by presenting meaningful and relevant material to learners, leading to deeper comprehension and long-term retention. It also discusses the importance of authentic language use in real-world contexts, which fosters language proficiency and communication skills.